Pengembangan Media Pembelajaran Handout Berbasis Discovery Learning Di SMAN 17 Luwu - Hasrah Hasrah; Khaerati Khaerati; Nur Muhajirah Yunus (IAIN Ternate, 2022)
This study aims to determine the results of the development of Discovery Learning-based Handout learning media at SMAN 17 Luwu. This type of research is R&D (Research and Development) which refers to the ADDIE development research design which consists of five stages, namely analysis, design, development, implementation and evaluation. The population of this study were all students of class XII SMAN 17 Luwu and the sample of this study was class XII MIPA 2 who were selected using a purposive sampling technique. The research instruments were in the form of validation sheets, questionnaires and learning achievement tests. Data analysis techniques used in this study are validity test, practicality test and effectiveness test. The results of research on the development of Handout learning media based on Discovery Learning at SMAN 17 Luwu show that: (1) media expert validation test data obtained a validity percentage of 87.5% (very valid) while material experts obtained 84.3% (valid) (2) test the practicality of the teacher's response to the product was 95% (very practical) while the student's response to the product was 71.05% (practical) (3) the effectiveness data was obtained 85% (very effective). The conclusion from the development of Discovery Learning-based Handout learning media can be used in Metabolism material at SMAN 17 Luwu.Keywords: development; handout learning media based on discovery learning